Support of the Critical Thinking Process in Synchronous Online Collaborative Discussion Through Model-Eliciting Activities - Weltzer-Ward, Lisa M; Carmona, Guadalupe (International Journal of Emerging Technologies in Learning (iJET), 2008)
As online education becomes common, it is essential to identify activities that support critical thinking in this environment. This paper describes the use of a model-eliciting activity (MEA) solved by groups in a synchronous online discussion. The participants displayed their thinking processes and solutions consistent with successful face-to-face (F2F) MEAs. Each groupâ??s discussion showed evidence of critical thinking and incorporated quality logical arguments. This demonstrates that MEAs may be also used in an online environment to successfully support application of critical thinking skills.